"Accoucheur of literature": Joseph Banks and the Philosophical Transactions, 1778–1820. (17th July 2020) - Moxham, Noah
Abstract: This paper explores the editorial influence of Joseph Banks on the Philosophical Transactions —still, at the time of his accession to the Presidency of the Royal Society in 1778, the most prestigious scientific periodical published in English. In particular, it examines how Banks forged, and wielded, personal influence over what went into the Transactions . Nominally, at least, the periodical was under the collective control of the Society's council, with significant statutory safeguards in place to prevent editorship by a presidential clique. Yet this was exactly what Banks was able to speedily create and maintain. In this essay I explore how Banks accomplished this and the pressures it produced, addressing two key questions. First, I examine the social dimension of Banks's management of the Transactions (and what contemporaries thought of it), including particularly the questions of how and to whom access to the periodical was afforded or denied by Banks and his associates; and second, I consider how Banks and the Society dealt with the emerging competitive pressure of new commercial and learned society periodicals. I outline a sphere of scientific sociability partly created by informal processes of communicating, circulating, and evaluating papers developed by Banks and his close associates, and its significance for the Transactions in its engagements with other sites, genres, and conventions of scientific publication.